The specific medications for pulmonary arterial hypertension at functional class III to IV: a systematic review and meta-analysis - Li, Qiang; Kuang, Hongyu; Yi, Qijian; Du, Huaan (Frontiers in Medicine, 2024)
Purpose To systematically evaluate the clinical efficacy and safety of targeted drugs in patients with pulmonary arterial hypertension (PAH) with cardiac function grades III–IV, and conduct a meta-analysis. Methods Two researchers independently searched the PubMed, EMBASE, and Cochrane Library databases for relevant studies, with the search period extending from the establishment of the databases to March 2024. Meta-analysis was performed using statistical software Review Manager 5.4. Heterogeneity among studies was analyzed using either a random-effects model or a fixed-effects model. When the I2 value was < 50%, indicating good homogeneity, the fixed-effects model was adopted; otherwise, the random-effects model was used. For continuous variables, the 6-minute walk distance (6MWD) was expressed as the mean difference (MD), while hemodynamic parameters were represented by the standard mean difference (SMD). For categorical variables, the odds ratio (OR) was used. The confidence interval (CI) was set at 95%, and a p < 0.05 was considered statistically significant. Results Ten randomized controlled trials (RCTs) involving 553 patients with PAH and cardiac function grades III-IV were ultimately included. Three RCTs targeted the endothelin pathway, five targeted the prostacyclin pathway, and two assessed the effects of combination therapy. Meta-analysis and subgroup analysis revealed that short-term monotherapy with bosentan significantly improved 6MWD by 53.67 m (95% CI: [43.57, 63.77] meters, p < 0.0001) in patients with FC III-IV PAH. Additionally, prostacyclin analogs increased 6MWD by approximately 25.02 meters (95% CI: [19.22, 30.81] meters, p < 0.0001) in this patient population. Further hemodynamic assessments demonstrated that both bosentan monotherapy and prostacyclin analog therapy significantly reduced pulmonary vascular resistance, with SMDs of −1.07 (95% CI [-2.08, −0.06], p = 0.04) and −1.26 (95% CI = [−2.21, −0.32], p = 0.009), respectively. Analysis of the clinical efficacy of combination therapy in PAH patients revealed that while it did not significantly improve 6MWD, cardiac function improved in 59.1% of patients (95% CI=[38.5%, 79.6%]). Safety analysis indicated that combination targeted therapy did not significantly increase the incidence of severe adverse events in PAH patients. Conclusion Monotherapy with targeted drugs is safe and effective for patients with PAH and cardiac function grades III-IV. Combination therapy can significantly improve cardiac dysfunction in these patients without significantly increasing the risk of severe adverse events. Therefore, bosentan and prostacyclin analogs are both safe and effective options for patients with PAH and cardiac function grades III-IV. However, early combination therapy may have added clinical value in improving exercise tolerance, cardiac function, and cardiovascular remodeling in this patient population.